“CLOSE TO REALITY”: THE CONTRIBUTION OF INSTITUTIONAL SCHOLARSHIPS PROGRAM INITIATION OF THE THEACHING PROFESSION FOR THE ACADEMIC FORMATION OF STUDENTS OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
The approach between university and school allowsundergraduate students, in the case of Physical Education students to be able to experience the teaching profession, an experience that begins with the knowledge of scholastic community to their intervention. It's from the Scholarship Program Initiation to Teaching Profession)that the academics have possibilities to build new teaching practices according to difficulties observed during visits in schools(TARDIF, 2010).This perspective has the objective to present the contributions of the PIBID in the continuing education of the Physical Education students, of Vale do Acaraú University, Sobral-CE. It's about a qualitative study,literature review,where the activities developed are prepared based on the interdisciplinary theme,started since March 2014.About the academic formation,CAPES (2014)emphasizes that its goal is to raise the quality of initial formation of undergraduate students,from the interaction between knowledge seen in higher education with the specificities found in basic education. PIBID has the innovative proposal to allow in the formation of graduate students. The experience between what is taught in theory with practical application in public schools.Facing the difficulties,the PIBID shown as a preparation for practice of teaching profession approaching undergraduate students in Physical Educationfrom the school reality, besides favoring the experience in teaching, research and extension.
Keywords: Formation. Physical education. PIBID